Instant Crime Scene Reporting (ICSR) - MdTarnsi @ Amir, Noor Aisha (Universiti Teknologi Petronas, 2004)
Almost everyday the newspaper, magazines and televisions bombards us with the heartbreaking news of increasing number of crimes committed all around the nation. Often the policeofficers have difficulties in enforcing the lawdue to lackof evidence and poor public cooperation especially involunteering to be a witness. The aim of the project is to create a MMS application to be used by the general public to allow them to lodge instant report on any crime scene that they have witnessed by providing a rough picture of the scene or potential suspect in assistance towards the investigations. Civilians can use MMS technology to send multimedia messages the police department reporting on various incidents such as traffic violations, robberies, vandalism and so forth. The proposed system is aimed to help the authorities to identify suspects, obtaining reliable evidence which enables them to conduct an effective investigation on the alleged crime. The research to be undertaken will involve delving into the nature of law enforcement in Malaysia as well as the mobile phone technology in general and in depth research on the MMS system and application development. The Rapid Application Development (RAD) has been chosen as methodology to be applied during the development ofthe system.